2015
DOI: 10.1016/j.jpain.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Inhaled Cannabis on Painful Diabetic Neuropathy

Abstract: A randomized, double-blinded, placebo controlled crossover study was conducted in 16 patients with painful diabetic peripheral neuropathy to assess the short-term efficacy and tolerability of inhaled cannabis. In a cross-over design, each participant was exposed to a single dosing session of placebo, low (1% tetrahydrocannabinol, THC), medium (4% THC), or high (7% THC) doses of cannabis. Baseline spontaneous pain, evoked pain and cognitive testing were performed. Subjects were then administered aerosolized can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
196
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 186 publications
(207 citation statements)
references
References 47 publications
5
196
1
5
Order By: Relevance
“…In 6 of the 7 cases, at least 1 record met the inclusion criteria of the systematic review [14][15][16][17][18][19]. Reviewer screening time took on average between 30 and 40 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…In 6 of the 7 cases, at least 1 record met the inclusion criteria of the systematic review [14][15][16][17][18][19]. Reviewer screening time took on average between 30 and 40 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…The pain reduction occurs within 1 week 231 . Inhaled cannabis reduced spontaneous pain associated PDN for a short duration in a dose-dependent fashion but had significant negative cognitive effects 232 . Nabilone was significantly better than placebo at reducing pain intensity and improving sleep quality 233 .…”
Section: Findings From Studies Grouped By Chronic Pain Syndromementioning
confidence: 98%
“…Several trials reported significant improvements in sleep, and there were no serious adverse events reported. 3 Since 2010, eight new studies have been published [35][36][37][38][39][40][41][42] ( Table 3). Seven of them were performed on patients with neuropathic pain and one on patients with chronic headache.…”
Section: Update On Clinical Studies On Cannabis and Painmentioning
confidence: 99%